Understanding Behavioristic Theory - Pramana, Maleluan (Yayasan Sembilan Pemuda Indonesia, 2024)
Behavioristic theory is changing student behavior from not being able to being able to or from not understanding to understanding. Behavioristic theory is able to show changes in behavior that are considered learning. In madrasa education, behavioristic theory is very relevant. This theory argues that stimulus and response through a reward board known as a “point system” can increase students’ desire to learn and worship. Thus, students are more motivated to study and worship. The Learning Menu, according to behavioristic learning theory, is a process of changing behavior caused by the interaction between stimulus and response. The concepts of behavioristic learning theory are negative or contrary to Islam. On the other hand, other learning theories do not conflict with Islam, so they need to be synthesized.